A Comparison of Activity of Selected Shoulder Girdle Muscles in Boxers during Punch Kick using Three Different Techniques - Morteza Madadi Shad; Nader Farahpour (Sport Sciences and Health Research)
The aim of this study was to measure the intensity of activity of shoulder girdle muscles in punch kick using three techniques: shadow boxing, punch against punching bag and punch against a real opponent. 10 elite boxers (age 24±3 yr, mass 78±24 kg and height 177±5 cm) and 10 amateur boxers (age 20±4 yr, mass 81±13 kg and height 173±8 cm) participate in this study. Surface electromyography (sEMG) was used to measure the activity of middle trapezius, anterior deltoid, middle deltoid, posterior deltoid, pectoralis major, biceps brachii and triceps brachii muscles of the punching arm. ANOVA with repeated measures was performed to statistically test the effect of three different techniques of punch kick. The effect of different skill level was tested by multivariate ANOVA (P≤0.05). The results showed that anterior deltoid had the greatest muscle activity and pectoralis major indicated the least activity during punch kick. The effect of these three techniques was significant (P=0.000) (considering no other factors). The shoulder girdle muscles required maximum and minimum muscle activity in punch against punching bag and shadow kick respectively. The effect of skill level showed no significant difference in the EMG activity of muscles (P=1.22). The obtained results suggested the presence of a goal-dependent muscle activity strategy in punch kick.